Optimization of Production Activated Carbon for Removal of Pharmaceuticals Waste Using Taguchi Method and Grey Relational Analysis - Jatmiko, Tri (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2020)
The development of the pharmaceutical industry has led to increased environmental pollution by pharmaceutical waste. This encourages efforts to develop effective and inexpensive pharmaceutical waste management. One effort to handle pharmaceutical waste is to use activated carbon. In the manufacture of activated carbon there are several factors that affect the quality and performance of activated carbon produced. This research seeks to determine the optimum factors in making activated carbon and study its performance in adsorbing pharmaceutical waste. Multi-response analysis based on the Taguchi Grey relational analysis method is used to determine the optimum conditions. The most influential factors in the production of activated carbon, respectively, are pyrolysis temperature (800°C), ratio of precursors and activating agents (1:1), residence time (150 minutes) and finally the type of activator (KOH).